Organizational integration of the IT function: A key enabler of firm capabilities and performance - Francesca Ricciardi; Alessandro Zardini; Cecilia Rossignoli (Journal of Innovation & Knowledge (JIK), 2018)
Organizational integration between intra- and inter-organizational subsystems is an important factor of operational coordination, innovation, and strategic effectiveness. Scholars have mainly focused on the organizational integration of three sub-systems: production/operations, marketing/sales, and R&D. This study explored the organizational integration of the organizational unit in charge of the firm's IT and information systems: the IT function. This construct has five key dimensions: integration of the IT function with top management, business units, customers, non-IT suppliers, and IT providers. Analysis of data from 236 responses to a survey questionnaire confirmed that all five dimensions positively influence the firm's market performance. The contribution of the firm's information systems to both competitive and cooperative organizational capabilities strongly mediates this relationship. This research model highlights the complementary explanatory power of Lawrence and Lorsch's (1967) theory of organizational integration, the business-IT alignment literature, and the resource-based view (RBV). The results suggest that the more firms evolve towards IT-enabled business environments, the more they need IT managers to be socially embedded in these environments and to contribute actively to the overall knowledge-based organizational integration of the system.
Keywords: M15; L2; 650; Organizational integration; Organizational units; IT management value; Competitive capabilities; Cooperative capabilities; CIO